On the origin of Anagyrus callidus (Hymenoptera: Encyrtidae), a parasitoid of pink hibiscus mealybug Maconellicoccus hirsutus (Hemiptera: Pseudococcidae) - Triapitsyn, Serguei V.; Andreason, Sharon A.; Dominguez, Chrysalyn; Perring, Thomas M. (Zootaxa, 2019)
Anagyrus callidus Triapitsyn, Andreason & Perring (Hymenoptera: Encyrtidae), recently described from southern California, USA and Mexico, is a primary parasitoid of the pink hibiscus mealybug, Maconellicoccus hirsutus (Green) (Hemiptera: Pseudococcidae). This wasp species previously was misidentified as Anagyrus kamali Moursi, which was introduced and released as such in the United States (California and Florida) and Mexico. In this paper, the origin of A. callidus is shown to be from Taiwan, based on differences in the morphology and molecular sequences of voucher specimens of an earlier colony of the misidentified A. kamali from Puerto Rico (released in August 2002 in southern Florida), and specimens that originated in southern Taiwan.